Małoletni podejrzani oraz oskarżeni i ich przedstawiciele ustawowi na tle zmian Kodeksu postępowania karnego wprowadzonych ustawą z dnia 14 kwietnia 2023 r. - Szczechowicz, Krystyna (PRAWO i WIĘŹ, 2025)
Representing a child in criminal proceedings is an issue that legislators worldwide are struggling with. This issue is particularly important when the perpetrator of the crime is a person below the age of 18, and they are trying to protect their rights as a suspect and accused. The aim of the article is to analyse the provisions introduced by the Act of 14 April 2023, amending the Act – Code of Criminal Procedure and certain other acts, that are intended to constitute the implementation of Directive 2016/800 on procedural guarantees for children who are suspects or defendants in criminal proceedings by Poland. The essence of the problem is whether the Polish legislator has met the requirements of the directive. The participation of representatives of the litigating parties in the preparatory and judicial proceedings, in addition to the activity of the litigants, is an additional guarantee of defending their procedural interests. The article points out that the Polish Code of Criminal Procedure, even after the changes, does not contain sufficient solutions in this respect, and it is necessary to implement legislative work aimed at the proper implementation of the directive and raising the standard of protection for children who are suspects or defendants in criminal proceedings.